A new approach to the problem of assessing the radon hazard of building sites - N. K. Ryzhakova; K. O. Stavitskaya; A. A. Udalov (Радиационная гигиена)
Radon and its daughter products create more than half dose from all natural radiation sources. The radon entering the buildings is emitted mainly from soils lying at the base of the foundation. Therefore, before carrying out construction work, the radon hazard of the construction area are determined. In the Russian Federation, the radon hazard of an area can be determined using radon flux density measured on the soil surface. To date, radon researchers came to the conclusion that the geology of the territory affects the amount of radon released from the soil surface. However, there are almost no studies devoted to the release of radon from the surface of various soil types. The paper presents the measuring results of the radon flux density on the surface of loess loams, porcelain clay, argillaceous slate, sand-and-gravel sediment, rocky limestone, clayey limestone, andesite-basalt porphyrite and quartzrock. The measurements were carried out by the accumulation chamber method using the Alfarad Plus measuring complex. Also, measuring radium activity concentration and soil moisture were carried out. The research demonstrates that, depending on the type of soil, the amount of radon emanating from its surface differs by more than an order of magnitude. The largest values of radon flux density of ~ 800 mBq∙m-2s-1 were recorded for andesite-basalt porphyrite and quartzrock. The smallest ones of ~ 40 mBq∙m-2s-1 were registered for loess loams and argillaceous slates. For soils consisting of small sand and clay grains, a rather strong dependence of the radon flux density on soil moisture was found. When measuring soils with low moisture (2-6%), a proportional dependence of the radium activity concentration on the amount of radon emanating from the soil surface is not observed. The types of soils that lie at the foundations of the buildings, and their physical properties can be used as the basis for classifying building sites according to the degree of radon hazard. Relevant information may be provided by organizations engaged in design and survey work at building plots. The approach proposed in the work for assessing radon hazard will allow avoiding labor-intensive measurements of radon and thereby reduce the financial, material and labor costs of building construction.